2017
DOI: 10.3201/eid2302.161564
|View full text |Cite
|
Sign up to set email alerts
|

Cutavirus in Cutaneous Malignant Melanoma

Abstract: A novel human protoparvovirus related to human bufavirus and preliminarily named cutavirus has been discovered. We detected cutavirus in a sample of cutaneous malignant melanoma by using viral enrichment and high-throughput sequencing. The role of cutaviruses in cutaneous cancers remains to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Thus far, human protoparvovirus DNA has been detected mainly in diarrheal feces and two studies have shown the presence of CuV DNA in altogether four malignant CTCL skin lesions and in one melanoma [1,6]. Immunosuppressed organ transplant recipients have in general been shown to be at risk for epithelial skin cancers [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, human protoparvovirus DNA has been detected mainly in diarrheal feces and two studies have shown the presence of CuV DNA in altogether four malignant CTCL skin lesions and in one melanoma [1,6]. Immunosuppressed organ transplant recipients have in general been shown to be at risk for epithelial skin cancers [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the original publication of CuV discovery, it was detected by PCR in 2/15 CTCL lesions, whereas 10 skin carcinomas, 16 other skin diseases (8 parapsoriasis, 4 eczema and 4 eczematoid dermatitis), and 3 healthy skin samples were all CuV-DNA negative [1]. Furthermore, one out of 10 melanoma skin samples was reported to harbor CuV DNA [6]. Interestingly, we discovered CuV DNA both in non-malignant and malignant skin of three subjects: two transplant recipients had CuV DNA in basal or squamous cell carcinoma tissue and in healthy skin, whereas one CTCL/MF patient had CuV in both early-and late-stage CTCL lesions, in melanoma, atypical moles, benign skin tumors, and lymph nodes, but not in his prostate samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin samples of other cancers ( n = 10) and non-malignant skin biopsies ( n = 19) were all CuV PCR-negative ( Table 3 ). Later on, CuV DNA was detected with NGS in the malignant skin lesions of one melanoma patient in Denmark [ 31 ], while 9 additional melanoma samples were CuV DNA-negative when using both NGS and PCR. The CuV nt sequence from Denmark was 96.5–93.7% identical to the previously published three sequences covering the entire NS1 and VP coding regions ( Table 4 , data calculated for this review, and Figure 1 ).…”
Section: Cutavirusmentioning
confidence: 99%
“…Advances in DNA sequencing technology have led to the discovery of several new members of the ssDNA Parvoviridae that infect humans, including human bocaviruses 1 to 4 (HBoV1-HBoV4), cutavirus (CuV), tusavirus (TuV), bufavirus 1 to 3 (BuV1-BuV3), and human parvovirus 4 (PARV4) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. These viruses are grouped into different genera based on the DNA sequence of their non-structural (NS) proteins [ 8 ].…”
Section: Introductionmentioning
confidence: 99%